Interpretation of ideological time markers through literary images of the kabardian prose writer M. Gubzhev - Khamisha T. Timizhev; Naima B. Bozieva (Кавказология, 2022)
The article is devoted to the study of the ideologically and thematically interconnected novels of the Kabardian writer M. Gubzhev (1913-1997) “The Clever Paves His Milky Way” and “The Two-Legged Wolf” in their national and genre-style specificity. For the first time, as the author’s individual skill is studied, his contribution to the development of the genre of the Kabardian novel is determined. The content and compositional features of the novels dedicated to the dramatic periods of the life of the Circassians in the entire country are determined. The scientific novelty of the proposed work consists in restoring the picture of the development of Kabardian literature, in correlating its most significant facts with the changing historical and cultural context and in particular in identifying the original features of the studied novels by M. Gubzhev. Today's themes of war and revolution are relevant. New accents appeared in the works of famous prose writers of the older generation. Indicative are the novels of M. Gubzhev, which are a highly artistic work of modern national literature. They raise the theme of the recent past, but the works show a novel approach, a view from the standpoint of today. The difficult time of collectivization, the post-war revival - the heroes of M. Gubzhev’s novels withstood all these tests with honor. Revealing in the novels the harsh drama of the path traversed by the heroes, the author embodies the historical experience of their native people in their destinies. The imagery, poetry of the language, colorful descriptions of the life and traditions of the Kabardians attract attention. The practical significance of the article is determined because the materials of this study can be used in the development of lecture courses on the history of Kabardian-Circassian literature, in preparing textbooks on literature, as well as in the writing of fundamental scientific research on individual representatives, specific periods and artistic phenomena of the literatures of peoples in South Russia.